Aiming clusters of heliostats over solar receivers for distributing heat flux using one variable per group. (November 2020) - García, Jesús; Barraza, Rodrigo; Soo Too, Yen Chean; Vásquez Padilla, Ricardo; Acosta, David; Estay, Danilo; Valdivia, Patricio
Abstract: The performance of solar central receivers is inherently linked to the aiming distribution/cluster of heliostats over the surface of solar receivers. A reliable methodology is necessary to maintain the lifespan of these costly devices. This research presents a method for manipulating the heliostats' aiming within a solar field by using a group behavior that relies on a single manipulated variable. This methodology addresses the problem by accounting for the heliostat position over the field, and a reduced number of the required groups. The work relies on the adaptation of an ordinary differential equation, commonly used to model conventional control valves, to establish the mean movement of the heliostats' aiming within the group. Afterward, these values are coupled to predefined paths that set the direction of motion for each point. It is shown that the proposed approach can promote changes in the heat flux profiles on the receiver, thereby allowing for the reduction of the peak heat fluxes about 30% of the initial value, while maintaining spillage below 15% for a spread aiming point distribution. Graphical abstract: Image 1 Highlights: Large groups of heliostats can work harmonized using a single primary signal. The behavior of the group adopts the working principle of a control valve. It enables the implementation of a vast amount of closed-loop control strategies. New strategies allow better distribution of solar radiation over central receivers. Reduction of heat flux peaks to 30% of the initial value with spillages below 15%.